2016
DOI: 10.1007/s00216-016-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

It is all about the solvent: on the importance of the mobile phase for ZIC-HILIC glycopeptide enrichment

Abstract: Glycopeptide enrichment is a crucial step in glycoproteomics for which hydrophilic interaction chromatography (HILIC) has extensively been applied due to its low bias towards different glycan types. A systematic evaluation of applicable HILIC mobile phases on glycopeptide enrichment efficiency and selectivity is, to date, however, still lacking. Here, we present a novel, simplified technique for HILIC enrichment termed “Drop-HILIC”, which was applied to systematically evaluate the mobile phase effect on ZIC-HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…HILIC is suitable for the analysis of polar analytes which are inadequately retained in RP-LC [1]. HILIC was successfully applied to glycopeptide enrichment [7,8], released glycan analysis [9,10], and separation of different glycoforms of peptides [11]. Although the directed analysis of glycoproteins provides site-specific information on glycans, the common approach to characterize glycans in HILIC is their enzymatic or chemical releas LC/MS analysis [12].…”
Section: Introductionmentioning
confidence: 99%
“…HILIC is suitable for the analysis of polar analytes which are inadequately retained in RP-LC [1]. HILIC was successfully applied to glycopeptide enrichment [7,8], released glycan analysis [9,10], and separation of different glycoforms of peptides [11]. Although the directed analysis of glycoproteins provides site-specific information on glycans, the common approach to characterize glycans in HILIC is their enzymatic or chemical releas LC/MS analysis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar glycopeptides from IgG1, IgG2, and IgG4 were finely separated on Glycan BEH Amide , TSKgel Amide‐80 , and Halo Penta‐HILIC . Sialylated glycopeptides on EEQYNSTYR and EEQFNSTFR were analyzed by Drop‐HILIC enrichment, followed by RPLC–ESI–MS/MS . The EEQYNSTYR glycopeptides is highly polar and hydrophilic, so completely aqueous conditions are required to trap it on RP phases.…”
Section: Analysis Of N‐ and O‐glycopeptidesmentioning
confidence: 99%
“…Hydrophilic Interaction Chromatography (HILIC) has extensively been applied for this purpose due to its low bias towards different glycan types. However, a recent systematic evaluation of the mobile phase effect on glycopeptide enrichment indicated that zwitterionic (ZIC)-HILIC glycopeptide efficiency primarily relied upon the used solvent 25 . Thus, if the analytical conditions allow the detection of glycopeptides from complex samples without any enrichment steps, any enrichment-derived bias would be significantly reduced.…”
Section: Rationale and Study Designmentioning
confidence: 99%
“…More importantly, glycopeptide enrichment efficiency was strongly dependent on the used organic phase 25 Figure S3; Figure 2 and Supplementary Table S4 and S5). Glycopeptides were generally detected in higher charge states when ACN was used as the dopant solvent.…”
Section: To Enrich or Not To Enrich-captivespray Nanobooster Enhancesmentioning
confidence: 99%